PENGARUH MODEL PEMBELAJARAN TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Noprida, Fransiska Santa; Astuti, Dwi; Ijuddin, Romal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to determine the effect of Two Stay Two Stray cooperative learning model type on SPLTV material to the mathematical communication ability of SMA Negeri 10 Pontianak. The form of this research is quasi experiment with posttest only control group design. The technique to be used is measurement techniques via written tests in the form of essays. The result of data analysis obtained from the students? mean score, the students? mean score of mathematical communication ability test of experiment class was 55,29 and the students? mean score of mathematical communication ability test of control class was 38,10. From the results of t test calculations, obtained tcount > ttable or 3.83 > 1.99 thus the students? mathematical communication ability with Two Stay Two Stray cooperative learning type significantly higher than students with conventional learning. Based on the effect size, the effect size score was 0.94, so the contribution of Two Stay Two Stray cooperative learning model type is included in the high criteria. Based on these data it can be concluded that Two Stay Two Stray cooperative learning type effect on the students? mathematical communication ability in SPLTV material in X grade students of SMA Negeri 10 Pontianak. Keywords:  Two Stay Two Stray Cooperative Type, Mathematical Communication Ability, SPLTV